2018
DOI: 10.1186/s12917-018-1575-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a rtPCR for the detection of virulent and benign Dichelobacter nodosus, the causative agent of ovine footrot, in Australia

Abstract: BackgroundOvine footrot is a highly contagious bacterial disease of sheep, costing the Australian sheep industry millions of dollars annually. Dichelobacter nodosus, the causative agent of footrot, is a gram-negative anaerobe classed into virulent and benign strains as determined by thermostability of their respective protesases. Current methods for detection of D. nodosus are difficult and time-consuming, however new molecular techniques capable of rapidly detecting and typing D. nodosus have been reported.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…It can be concluded that clinical features are consistent with the PCR classification if benign is defined as non-progressive in the South German sheep population. This is in line with findings from Locher et al [27] in a previous study on clinically free sheep flocks in Switzerland, was described in Australia by Best et al [29] and also reported from Norwegian farms by Vatn et al [28]. Further, Best et al [29] proofed, that real-time PCR was significantly more sensitive in detection of aprV2 in clinically healthy sheep compared with culture/gelatinase test.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It can be concluded that clinical features are consistent with the PCR classification if benign is defined as non-progressive in the South German sheep population. This is in line with findings from Locher et al [27] in a previous study on clinically free sheep flocks in Switzerland, was described in Australia by Best et al [29] and also reported from Norwegian farms by Vatn et al [28]. Further, Best et al [29] proofed, that real-time PCR was significantly more sensitive in detection of aprV2 in clinically healthy sheep compared with culture/gelatinase test.…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with findings from Locher et al [27] in a previous study on clinically free sheep flocks in Switzerland, was described in Australia by Best et al [29] and also reported from Norwegian farms by Vatn et al [28]. Further, Best et al [29] proofed, that real-time PCR was significantly more sensitive in detection of aprV2 in clinically healthy sheep compared with culture/gelatinase test. McPherson et al stated, that the results of the realtime PCR did not agree sufficiently with the clinical findings in Australian sheep flocks and therefore depended on additional culturing [30].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In another South East Australian study, the aprV2 positive D. nodosus gene was detected in 45% of the 11 clinically healthy flocks, and in 100% of the 13 flocks clinically affected by footrot, suggesting that the virulent genotype can be present in sheep without causing disease. 16 The collection of samples over multiple seasons in this study should have ensured a better correlation between the aprV2 positive D. nodosus and clinical disease, as a proportion of the samples were collected under favourable conditions for footrot expression.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Genomic methods were reported to distinguish between virulent and benign strains of D. nodosus using polymerase chain reaction (PCR) of the apr2 gene directly from sheep foot swabs. 15 While one Australian study demonstrated correlations between the prevalence of the virulent aprV2 gene in foot swabs by real-time PCR and clinical signs of footrot, 16 another showed significant disagreement between the aprV2 positive PCR samples and field diagnosis. 14 Sheep can be infected with multiple strains of D. nodosus, so foot swabs may contain a mixture of both virulent and benign D. nodosus.…”
mentioning
confidence: 99%